2022
DOI: 10.3390/bs12060169
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Videoconferencing on Second-Language Learning: A Meta-Analysis

Abstract: To mitigate the unexpected closure of educational institutions during the COVID-19 pandemic, e-learning has become a practical alternative to conventional face-to-face instruction. Videoconferencing, a synchronous computer-mediated communication (SCMC) approach, has been adopted as a venue to continue student learning activities. However, in the field of second-language (L2) education, videoconferencing had already been integrated into learning tasks, enabling L2 learners to have more opportunities to access a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…These features are embedded in many VC tools and can also be supported by other external online tools and platforms including YouTube videos, podcasts, Google Docs, Voice thread, Wordwall activities, LearningApps activities, wikis, online websites, and social media, etc. (Asoodar et al, 2016;Yu, 2022). Another benefit is the ability to switch off the camera during speaking activities, which can improve student motivation and confidence (Lee, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These features are embedded in many VC tools and can also be supported by other external online tools and platforms including YouTube videos, podcasts, Google Docs, Voice thread, Wordwall activities, LearningApps activities, wikis, online websites, and social media, etc. (Asoodar et al, 2016;Yu, 2022). Another benefit is the ability to switch off the camera during speaking activities, which can improve student motivation and confidence (Lee, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is also worth noticing that CMC, as mentioned earlier, is not a simple uniform construct, but rather a broad theme involving various intricacies, such as different forms (synchronous and asynchronous) and modes (text-based, audio-based, and video-based) (Yu, 2022). This within-group heterogeneity has received increasing attention in more recent studies, with fewer and fewer researchers employing the broad term "CMC" and instead opting for specific terms like "SCMC" or "ACMC."…”
Section: Synchronous Computer-mediated Communication (Scmc)mentioning
confidence: 99%
“…It also enables learners to reach audiences beyond their classmates and teachers and expand their learning environment. Interactive, communicative tasks can be conducted via videoconferencing for language learners to use a wide variety of communicative strategies and sharpen their language abilities ( Cirit-Işıklıgil et al, 2023 ), whose effectiveness has been demonstrated in recent review studies ( Ibrahim and Hashim, 2021 ; Yu, 2022 ).…”
Section: Introductionmentioning
confidence: 99%